Peran Mediasi dalam Penyelesaian Sengketa Perjanjian Kontrak Bisnis di Indonesia - Simarmata, Boy Gabriel Yohanes; Sinaga, Irene Putri Alfani Sofia (Universitas Muhammadiyah Ponorogo, 2025)
Business contract disputes are common issues in the business world, arising from either breaches of agreements or differing interpretations of contract terms. Dispute resolution through litigation often takes a long time, incurs high costs, and has the potential to damage established business relationships. This study aims to analyze the role of mediation in resolving business contract disputes in Indonesia by highlighting its effectiveness, challenges, and opportunities for optimization within legal and practical contexts. This research employs a normative legal method with an analytical approach to relevant regulations, such as Supreme Court Regulation (Perma) No. 1 of 2016 on Mediation Procedures in Court, as well as legal doctrines and related literature. The findings indicate that mediation has great potential as a more efficient dispute resolution mechanism than litigation, as it is flexible, faster, and helps maintain business relationships between parties. However, its implementation still faces obstacles, including low awareness among business actors, a limited number of professional mediators, and a dominant litigation culture. The originality of this study lies in its comprehensive analysis of mediation implementation based on regulatory reviews and business practices in Indonesia, along with strategic recommendations to enhance its effectiveness. The study's limitations include constraints in empirical data collection, as it primarily adopts a normative approach. Therefore, further research based on case studies or interviews with legal practitioners and professional mediators is recommended to gain deeper insights into the practical effectiveness of mediation. To address existing challenges, efforts are needed to promote mediation awareness, improve mediator competencies, and strengthen regulations supporting out-of-court mediation.